The Effect of Pilates Training on the Balance of Elderly - Kristina Zaičenkovienė; Renata Rakovaitė (Lithuanian Sports University, 2019)
Research background. Falling is one of the most important problems in the elderly's mobility disorder, which is most often affected by the loss of balance. It is known that Pilates exercises could help to increase the deep muscle strength, improve posture and proprioception, which affects the improvement of the balance. Objective - to evaluate the effects of Pilates exercises on the elderly's static and dynamic balance. Methodology. The study population consisted of 20 volunteers, men and women, who were divided into Pilates exercises (n = 10, age 65.1 ± 2.6) and control (n = 10, age 68.6 ± 4.9) groups. The study group participated in Pilates classes 2 times per week for six weeks (session duration 60 minutes). The control group did not participate in any physical activity, but they were physically active as usually in their daily life. The main outcome measures were assessed before and after the intervention. The static balance was assessed by measuring posturographic parameters using the force platform, dynamic balance was measured with the Timed up and Go Test (TUG) and the Four Square Step Test (FSST). Results. The results showed signifcant improvement in static balance of the experimental group after the Pilates exercises during standing tests when the feet were apart, eyes opened and closed and when the feet together with eyes opened, and when the foot was in front of the other foot. The results of the control group did not differ during both tests. The results of both groups did not differ in the static balance tests before and after the study, but after the Pilates exercises, the results of the Pilates group signifcantly differed from the control group test results when the feet were in shoulder line with open eyes. The results of the dynamic balance after Pilates exercises signifcantly improved in both tests in the study group. Before the study, there were not statistically signifcant differences in the dynamic balance results between the groups. Conclusions. Six-week Pilates exercises had a positive effect on the elderly's static and dynamic balance. Keywords: Pilates training, static balance, dynamic balance.